(untitled) (Global Journal of Science Frontier Research, 2023)
The objective of this work is to develop and optimise the ESSP841/CRP999 real-time PCR targeting the 18S ribosomal rRNA of Eimeridae (Eimeria spp) found in Mugil cephalus from the east coast of Algeria and to determine their pathogenicity and the risk of contamination of consumers. Mugilidae from the east coast of Algeria were captured in search of parasites that could infect them. In the laboratory 816 Mugil cephalus were weighed, dissected and eviscerated. In our study we found 378 samples positive for Eiemeria sp (46.3%) out of 816 fish samples, i.e. a prevalence of 46.3%, the average intensity was 1.6. The results of the direct examinations are confirmed by real-time PCR using the primer pair ESSP841 CRP999 which was positive for all samples tested. We obtained curves with variable TCs.